2018
DOI: 10.1155/2018/5231931
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Sudden Onset of Spinal Epidural Angiolipoma

Abstract: Angiolipomas are relatively rare benign tumors. Spinal angiolipomas that generally induce slow progressive cord compression are most commonly found in the thoracic region. A 49-year-old female with obesity presented with a 1-week history of progressively worsening back pain, paresthesia of lower limbs, and gait disturbance. When thoracic magnetic resonance imaging (MRI) revealed a dorsal epidural mass at the Th5–Th8 level, the patient underwent a laminectomy for gross total excision of the lesion. Both mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In this case the final pathology was angiolipoma. While considered a benign lesion, neurologic decline can occur with hemorrhage, intratumoral thrombosis, or steal phenomenon [4][5].…”
Section: Discussionmentioning
confidence: 99%
“…In this case the final pathology was angiolipoma. While considered a benign lesion, neurologic decline can occur with hemorrhage, intratumoral thrombosis, or steal phenomenon [4][5].…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 26 , 27 Critical onset or aggravated neurological symptoms occur if the lesion grows rapidly because of tumor thrombosis and/or hemorrhage. 28 31 …”
Section: Discussionmentioning
confidence: 99%
“…22,26,27 Critical onset or aggravated neurological symptoms occur if the lesion grows rapidly because of tumor thrombosis and/or hemorrhage. [28][29][30][31] X-rays of the spine often show negative results in patients with SALs, but might show erosion of the walls of the bodies and pedicles as a result of infiltrating tumors. 8,32 Myelography was performed in some cases and showed a characteristic posterior extradural spinal lesion with partial or complete filling defect.…”
Section: Discussionmentioning
confidence: 99%
“…This was a case of a 47-year-old male who developed sudden paresthesia and complete neurological palsy within a few minutes due to the hemorrhagic epidural angiolipoma. In 2018 Horiuchi et al [4] reported the case of a 49-yearold female with obesity (BMI, 31.1 kg/m 2 ) who presented with a 1-week history of progressively worsening back pain, paresthesia of the lower limbs, and gait disturbance. Surgery was performed and angiolipoma was diagnosed on the pathological examination after surgery.…”
Section: B C Amentioning
confidence: 99%
“…Most spinal angiolipoma are expressed at the thoracic level and are associated with signs of cord compression as they enlarge slowly, therefore, a sudden deterioration in symptoms does not occur. However, hemorrhagic transformation of angiolipoma, although rare, may cause sudden worsening of neurological symptoms [3][4][5]. Unfortunately, it is difficult to differentiate these cases from simple hematoma.…”
mentioning
confidence: 99%